Customer Satisfaction and Repurchase Intention in Terms of E-Commerce Logistics Service Quality and Recovery Service - Amma Fazizah; Rakhmawati, Antin; Eko Agus Alfianto; Dewi Nikmatul Husnah (SKeTsa Bisnis (e-jurnal), 2024)
Abstract The shift from traditional markets to digital markets makes the community's need for expedition services very high. The increasing number of business competitors in electronic services requires companies to always pay attention to consumer needs and try to meet consumer expectations by providing quality electronic services that can create customer satisfaction. This study aims to determine the effect of E-Service Quality and E-Recovery Service on Repurchase Intention through Customer Satisfaction as a mediating variable. The type of research used is explanatory research with a quantitative approach. The sample is 100 respondents who are J&T Express Indonesia customers who have submitted complaints to the X @jntexpressid. Data analysis used is PLS- SEM analysis with mediating effect. The results showed that: the E-Service Quality had a significant direct and indirect effect on Repurchase Intention through Customer Satisfaction;variable E-Recovery Service is not a significant direct effect on Repurchase Intention but an indirect significant effect on Repurchase Intention through Customer Satisfaction; Customer Satisfaction as a mediating variable significant effect on Repurchase Intention. Abstrak Pergeseran pasar tradisional ke pasar digital menjadikan kebutuhan masyarakat akan jasa ekspedisi sangat tinggi. Meningkatnya jumlah pesaing bisnis dalam layanan elektronik menuntut perusahaan untuk selalu memperhatikan kebutuhan konsumen serta berusaha memenuhi harapan konsumen dengan memberikan kualitas pelayanan elektronik yang dapat menciptakan kepuasan konsumen. Penelitian ini bertujuan untuk mengetahui pengaruh E-Service Quality dan E-Recovery Service terhadap Repurchase Intention melalui Customer Satisfaction sebagai variabel mediasi. Jenis penelitian yang digunakan adalah explanatory research dengan pendekatan kuantitatif. Sampel sebanyak 100 responden yang merupakan pelanggan J&T Express Indonesia yang pernah mengajukan keluhan kepada akun X @jntexpressid. Analisis data yang digunakan adalah analisis PLS-SEM dengan efek mediasi. Hasil penelitian menunjukkan bahwa: variabel E-Service Quality berpengaruh signifikan secara langsung dan tidak langsung terhadap Repurchase Intention melalui Customer Satisfaction; variabel E-Recovery Service tidak berpengaruh signifikan secara langsung terhadap Repurchase Intention namun berpengaruh signifikan secara tidak langsung terhadap Repurchase Intention melalui Customer Satisfaction; Customer Satisfaction sebagai variabel mediasi berpengaruh signifikan terhadap Repurchase Intention.